PENGARUH COMPETITION INTENSITY TERHADAP EARNINGS MANAGEMENT MELALUI EXECUTIVE COMPENSATION SEBAGAI VARIABEL INTERVENING PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA DI SURABAYA DAN SIDOARJO - Friszha Prawindah Wardhany; Devie Devie (Business Accounting Review, 2016)
The Affect Of Competition Intensity On Earnings Management Through Executive Compensation As Intervening Variable in Manufacturing Industry Listed In Bursa Efek Indonesia in Surabaya and Sidoarjo. This study aimed to examine the direct and significant affect of competition intensity to earnings management through executive compensation in manufacturing industry listed in Bursa Efek Indonesia in Surabaya and Sidoarjo. This study used quantitative approach, and the data obtained through the distribution of questionnaires and used ratio financial statement analysis in go public manufacturing firms in Surabaya and Sidoarjo and processed by using SmartPLS software. This study showed that there was positive and significant relationship of competition intensity to executive compensation, competition intensity to earnings management,and there was negative and significant relationship of executive compensation to earnings management manufacturing industry listed in Bursa Efek Indonesia in Surabaya and Sidoarjo. Executive compensation became the intervening variables between competition intensity and earnings management.